Understanding hydrazine oxidation electrocatalysis on undoped carbon. Issue 17 (13th April 2022) - Burshtein, Tomer Y.; Tamakuwala, Kesha; Sananis, Matan; Grinberg, Ilya; Samala, Nagaprasad Reddy; Eisenberg, David
Abstract : The catalytic role of the most abundant component in Fe–N–C electrocatalysts – the carbon matrix – is investigated towards the hydrazine oxidation reaction in alkaline media, revealing the central role of edge defects in the activity. Abstract : Carbons are ubiquitous electrocatalytic supports for various energy-related transformations, especially in fuel cells. Doped carbons such as Fe–N–C materials are particularly active towards the oxidation of hydrazine, an alternative fuel and hydrogen carrier. However, there is little discussion of the electrocatalytic role of the most abundant component – the carbon matrix – towards the hydrazine oxidation reaction (HzOR). We present a systematic investigation of undoped graphitic carbons towards the HzOR in alkaline electrolyte. Using highly oriented pyrolytic graphite electrodes, as well as graphite powders enriched in either basal planes or edge defects, we demonstrate that edge defects are the most active catalytic sites during hydrazine oxidation electrocatalysis. Theoretical DFT calculations support and explain the mechanism of HzOR on carbon edges, identifying unsaturated graphene armchair defects as the most likely active sites. Finally, these findings explain the 'double peak' voltammetric feature observed on many doped carbons during the HzOR.